Practical Design Considerations for Performance and Robustness in the Face of Uncertain Flexible Dynamics in Space Manipulators - Holmes, Connor (Frontiers in Robotics and AI, 2021)
Low frequency dynamics introduced by structural flexibility can result in considerable performance degradation and even instability in on-orbit, robotic manipulators. Although there is a wealth of literature that addresses this problem, the author has found that many advanced solutions are often precluded by practical considerations. However, robust control of these manipulators on-orbit is tractable using practical controls methods. This paper investigates a pragmatic engineering approach that evaluates the system’s stability margins in the face of uncertain, flexible perturbation dynamics with frequencies that lie close to or within the bandwidth of the nominal closed-loop system. The approach results in constraints on the open-loop control bandwidth of the nominal control law (as designed for the rigid plant) and is shown to match well with heuristic methods commonly used to reduce the effect of unmodeled dynamics in control systems. Namely, the control system is designed to have a bandwidth that is lower than the minimum flexible mode frequency of the unmodeled dynamics by a given factor. The approach is considered in the context of both collocated (joint rate) and non-collocated (force/torque and vision-based) feedback.